2022
DOI: 10.1253/circj.cj-22-0332
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Magnetically Levitated Left Ventricular Assist Device in Advanced Heart Failure ― The Japanese Cohort ―

Abstract: LVADs, many patients still experience LVAD-specific complications such as stroke, infections (including driveline exit site or the LVAD pump itself), and device failure. 6-8 HeartMate 3 (HM3; Abbott Laboratories, Chicago, IL, USA) which is a fully magnetically levitated centrifugalflow pump, was developed as a next-generation LVAD. Several international trials have already demonstrated its superiority over previous axial-flow pumps for event-free survival. 9,10The clinical outcomes of LVADs with axial-flow pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…36 A recent multi-center study conducted in Japan demonstrated a significantly reduced stroke event in relatively small patients with a HeartMate 3 as compared with a HeartMate II. 37 Thus, low pump flow may not be a significant risk factor for strokes in patients with a HeartMate 3, which features a fully magnetically levitated centrifugal-flow pump, though further study is needed. Another feature of Japanese patients is prolonged support duration before heart transplantation because of the severe donor shortage.…”
Section: Hemocompatibility-related Complications Including Stroke And...mentioning
confidence: 98%
See 1 more Smart Citation
“…36 A recent multi-center study conducted in Japan demonstrated a significantly reduced stroke event in relatively small patients with a HeartMate 3 as compared with a HeartMate II. 37 Thus, low pump flow may not be a significant risk factor for strokes in patients with a HeartMate 3, which features a fully magnetically levitated centrifugal-flow pump, though further study is needed. Another feature of Japanese patients is prolonged support duration before heart transplantation because of the severe donor shortage.…”
Section: Hemocompatibility-related Complications Including Stroke And...mentioning
confidence: 98%
“…Therefore, preoperative evaluations of the chest wall and left ventricular apex by 3D CT scanning is important especially for small patients to prevent suboptimal positioning of the inflow cannula 36 . A recent multi‐center study conducted in Japan demonstrated a significantly reduced stroke event in relatively small patients with a HeartMate 3 as compared with a HeartMate II 37 . Thus, low pump flow may not be a significant risk factor for strokes in patients with a HeartMate 3, which features a fully magnetically levitated centrifugal‐flow pump, though further study is needed.…”
Section: Durable Mechanical Circulatory Support For End‐stage Heart F...mentioning
confidence: 99%